Smart Management Using Politics in Organizations - Butcher, D.; Clarke, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
The second edition extends the influential ideas developed in the original book with more practical advice about working with organizational politics for personal and organizational benefit. Drawing on recent research, with updated examples, it provides an essential and practical insight into the centrality of politics in organizational life.
Keywords: International business enterprises; Management; International Business; Management